PENGUJIAN AKTIVITAS EKSTRAK ETANOL KULIT BUAH KECOMBRANG (Etlingera elatior (Jack) R.M.Sm) SEBAGAI INHIBITOR TIROSINASE - Widiastuti, Harti; Abidin, Zainal (Jurnal Ilmiah As-Syifaa, 2021)
Healthy skin should have a flat surface, the texture is soft, elastic, and have the same skin color. Skin color is determined by the size, number and distribution of melanin pigment. Pigment brownish pigment melanin is to protect the skin from UV light scattering. An enzyme that plays a role in this browning reaction is tyrosinase. Browning reaction tyrosinase inhibitor can be inhibited by an enzymatic by an enzymatic reaction in the form of ions or molecules called tyrosinase. Inhibition of tyrosinase is one way to prevent skin hyperpigmentation. Tyrosinase enzyme catalyzes two main reactions in the biosynthesis of melanin, the hydroxylation of L-tyrosin into L-dopa and the oxidation of L-dopa becomes dopakuinon. Polyphenol compounds (Flavonoids) the group is basically have the effect cant inhibit melanogenesis as a tyrosinase inhibitor. Kecombrang a wild plant that has many benefits one of them as a source of natural antioxidants. Based on this research is conducted on the fruit skin kecombrang to see the activity of the enzyme tyrosinase barriers and whether rind kecombrang can inhibit tyrosinase enzyme and with the aim to utilize natural materials and waste that can inhibit the enzyme tyrosinase and can be used as a skin whitheter.Research iniated by the extraction of fruit skins kecombrang using etanol. Flavonid content test on the sample using Mg powder and HCl p, the results show a color change from dark brown to yellow. So positive it contains flavonoids. Measurements were contucted on a maximum wavelength of 478,003 nm, using the substrate L-tyrosine and the enzyme tyrosinase. Using comparators hidroquinon. Of the results of this study concluded that kecombrang fruit peel ectract at a concentration of 2 mg/mL could inhibit amounted to 55,92% and a concentration of 2,5 mg/mL could inhibit amounted to 56,58%.